Negative circular polarization emissions from WSe2/MoSe2 commensurate heterobilayers - Wei-Ting Hsu (Nature Portfolio, 2018)
The interlayer coupling in van der Waals heterostructures is sensitive to the interlayer atomic registry. Here, the authors investigate the polarisation properties of epitaxially grown, commensurate WSe2/MoSe2 heterobilayers with well-defined atomic registry, and observe negative, circularly polarized photoluminescence from interlayer excitons.